Network fundamentals : CCNA exploration companion guide - Dye, Mark A. (Cisco Press, 2008)
"...the official supplemental textbook for the Network Fundamentals course in the Cisco® Networking Academy® CCNA® Exploration curriculum version 4. The course, the first of four in the new curriculum, is based on a top-down approach to networking. The book's features reinforce the material in the course."--Back cover.